Analysis of Natural Day Lighting Concepts in Al-Raudhah Mosque in Medan, North Sumatra, Indonesia - Aziizah, Qaanitah; Nuraini, Cut; Syam, Fariz Harindra (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Al-Raudhah Mosque in Medan demonstrates a good application of natural lighting, considering its function as a place of worship requiring optimal lighting. The aim of the research is to understand the lighting concept in the Al-Raudhah Mosque, Medan. This qualitative research uses a descriptive-explorative method. Primary data were obtained through direct surveys of the object being studied. Secondary data collection was sourced from literature studies. The results of the research show that the natural lighting concept in the Al-Raudhah Mosque involves four strategies: 1) Building Orientation, 2) Design of Openings (Doors, Windows, Ventilation), 3) Use of Reflective Materials, and 4) Use of Bright Colors. The building's orientation takes into account its position relative to surrounding elements and structures.